Atomistic Frictional Properties of the C(100)2x1-H Surface. (3rd February 2013) - Jones, Paul M.; Tang, Huan; Hsia, Yiao-Tee; Yan, Xiaoping; Kiely, James D.; Huang, Junwei; Platt, Christopher; Ma, Xiaoding; Stirniman, Michael; Dinh, Lang
Abstract : Density functional theory- (DFT-) based ab initio calculations were used to investigate the surface-to-surface interaction and frictional behavior of two hydrogenated C(100) dimer surfaces. A monolayer of hydrogen atoms was applied to the fully relaxed C(100)2x1 surface having rows of C=C dimers with a bond length of 1.39 Å. The obtained C(100)2x1-H surfaces (C–H bond length 1.15 Å) were placed in a large vacuum space and translated toward each other. A cohesive state at a surface separation of 4.32 Å that is stabilized by approximately 0.42 eV was observed. An increase in the charge separation in the surface dimer was calculated at this separation having a 0.04 e transfer from the hydrogen atom to the carbon atom. The Mayer bond orders were calculated for the C–C and C–H bonds and were found to be 0.962 and 0.947, respectively. σ C–H bonds did not change substantially from the fully separated state. A significant decrease in the electron density difference between the hydrogen atoms on opposite surfaces was seen and assigned to the effects of Pauli repulsion. The surfaces were translated relative to each other in the (100) plane, and the friction force was obtained as a function of slab spacing, which yielded a 0.157 coefficient of friction.